2016
DOI: 10.1038/cr.2016.55
|View full text |Cite
|
Sign up to set email alerts
|

Long-term in vivo single-cell tracking reveals the switch of migration patterns in adult-born juxtaglomerular cells of the mouse olfactory bulb

Abstract: The behavior of adult-born cells can be easily monitored in cell culture or in lower model organisms, but longitudinal observation of individual mammalian adult-born cells in their native microenvironment still proves to be a challenge. Here we have established an approach named optical cell positioning system for long-term in vivo single-cell tracking, which integrates red-green-blue cell labeling with repeated angiography. By combining this approach with in vivo two-photon imaging technique, we characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(72 citation statements)
references
References 45 publications
9
63
0
Order By: Relevance
“…Contrary to GC precursors, PGN precursors were not affected by Kir2.1 mediated hyperpolarization suggesting that the recruitment of future PGNs is not activity-dependent. This is in line with findings that knocking out serotonin receptors did no affect cell density in the glomerular layer (Garcia-Gonzalez et al, 2017) and results showing that the migration of PGN precursors in the GL does not depend on sensory activity (Liang et al, 2016). Of note, this later study also showed that PGN neurons migrate for an extended period in the GL while most GCs had settled.…”
Section: Discussionsupporting
confidence: 89%
“…Contrary to GC precursors, PGN precursors were not affected by Kir2.1 mediated hyperpolarization suggesting that the recruitment of future PGNs is not activity-dependent. This is in line with findings that knocking out serotonin receptors did no affect cell density in the glomerular layer (Garcia-Gonzalez et al, 2017) and results showing that the migration of PGN precursors in the GL does not depend on sensory activity (Liang et al, 2016). Of note, this later study also showed that PGN neurons migrate for an extended period in the GL while most GCs had settled.…”
Section: Discussionsupporting
confidence: 89%
“…7 in ref. 12). In total, 91.21% of adult-born JGNs (83/91 cells) were eliminated between DPI 12 and DPI 28, with no cells eliminated after DPI 34.…”
Section: Longitudinal In Vivo Mapping Of Adult-born Juxtaglomerular Nmentioning
confidence: 95%
“…1f) and the rest was classified as uncertain cells. The cell turnover within the FOVs was fast during the pre-integration phase 12 (DPI 12-25) and substantially slower at later time points ( Fig. 1g), with the cumulative fraction of eliminated cells increasing almost linearly from DPI 12 to DPI 34 ( Fig.…”
Section: Longitudinal In Vivo Mapping Of Adult-born Juxtaglomerular Nmentioning
confidence: 96%
See 1 more Smart Citation
“…While dynamics of neuroblast migration have been elucidated in acute slice cultures (Luskin and Boone 1994, Koizumi, Higginbotham et al 2006, Nam, Kim et al 2007, Martinez-Molina, Kim et al 2011, Khlghatyan and Saghatelyan 2012), assessing the effects of olfactory input on RMS dynamics in vivo has been challenging due to a lack of tools that can monitor the long migratory path and that allow for longitudinal experimentation in live animals. Two-photon imaging techniques are useful for studying of the superficial areas in the OB such as the glomerular layer (Sawada, Kaneko et al 2011, Liang, Li et al 2016). However, these tools cannot image long-distance migration of the cells from the SVZ to the olfactory bulb in vivo.…”
Section: Introductionmentioning
confidence: 99%